(untitled) (Research, Society and Development, 2020)
With a case study, a field research was developed combining, exploration and description with a qualitative analysis, with the use of intensive direct observation technique, with the objective of the article to make an improvement in its process of remelting to increase its production capacity. The case study was carried out at Alcoa, the world leader in aluminum production, at work we went through a conceptual definition of aluminum alloy and its manufacturing process, which is currently of great relevance in the industrial market, due to its flexibility of application in various sectors. The improvement presented in the study allowed an increase in production in the process of remelting in the manufacture of aluminum alloy that was considered a bottleneck.